Pengaruh Pengetahuan Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Brebes - Kartika Nurul Aeni; Anisa Sains Kharisma; Titi Rahmawati; Roni; Amelia Sholeha (Journal of Accounting and Finance (JACFIN), 2020)
Taxes are people's contributions to the state treasury based on the law (which are enforced) by not getting reciprocal services that can be shown and used to pay taxes. There are factors that affect taxpayer compliance when paying PKB, one of which is tax knowledge, tax sanctions and taxpayer compliance. The sample used was 50 motor vehicle taxpayers using a distributed questionnaire. This study uses sampling with the accidental sampling method, which is a sampling method by taking respondents who happen to meet with the researcher, the sample can be used, if it is seen that the person is suitable as a data source. In this study to test the hypothesis whether there is a significant effect between tax knowledge and tax sanctions with taxpayer compliance in paying motor vehicle taxes at the Brebes SAMSAT. counted as 5,526. This shows that the tax variable (X2) has a significant effect on the motorized vehicle taxpayer compliance variable (Y) in SAMSAT Brebes. There is a significant effect between tax taxes and taxpayer compliance in paying motor vehicle taxes at SAMSAT Brebes.